Діагностика конкурентного середовища на вітчизняних продовольчих ринках - Страшинська, Лариса Володимирівна; Ткачук (Стахурська), Світлана Валеріївна; Худолій, Діана Юріївна (My University, 2021)
У статті проаналізовано конкурентне середовище та рівень інтенсивності конкурентної боротьби на молочному та кондитерському ринках. Визначено, що ринок молока питного (фасованого) є безпечним для конкуренції і достатньо відкритим для входження нових підприємств на нього. Про це свідчать як значення індексу, так й інші умови безпечності конкуренції. Досліджено, що розвиток ринку кондитерських виробів демонструє протилежні тенденції функціонування та потребує якнайшвидшого втручання держави в його діяльність. Запропоновано основні форми державного регулювання конкурентного середовища відповідно до специфіки галузі, які мають охоплювати наступні три напрями: правовий, стимулюючий та імперативний. Окреслено характеристику цих напрямів та основні важелі державного впливу. Наголошено, що саме за допомогою імперативних чинників можливо забезпечити прозорість конкурентних відносин на кондитерському ринку. В статье проанализированы конкурентная среда и уровень интенсивности конкурентной борьбы на молочном и кондитерском рынках. Определено, что рынок молока питьевого является безопасным для конкуренции и достаточно открытым для вхождения на него новых предприятий. Об этом свидетельствуют как значение индекса, так и другие условия безопасности конкуренции. Доказано, что развитие рынка кондитерских изделий демонстрирует противоположные тенденции и требует вмешательства государства. Предложены основные формы государственного регулирования конкурентной среды в соответствии со спецификой отрасли, которые должны охватывать следующие направления: правовое, стимулирующие и императивное. Определены характеристики этих направлений и основные рычаги государственного воздействия. Отмечено, что именно с помощью императивных факторов возможно обеспечить прозрачность конкурентных отношений на кондитерском рынке. The article uses the calculation of the Hirschman-Harfindel index to analyze the competitive environment and the level of intensity of competition in the dairy and confectionery markets. Based on the analysis, it was determined that the market of drinking milk (packaged) is safe for competition and open enough for new companies to enter it. This is evidenced by both the value of the index and other conditions of competition security. The whole milk market has shown similar development trends. It is proved that this market during January-August 2018 and 2019 was also favorable for competition, which provided an opportunity for the development of both existing enterprises and the emergence of new competitors. It is investigated that the development of the confectionery market demonstrates opposite tendencies of functioning. Its extremely high monopolization contributes to the fact that almost all its participants fall under the price and product press of the corporation "ROSHEN", which is a monopolist in this market. It is substantiated that the confectionery market requires the state intervention in its activities as soon as possible. Encouraging fair competition, preventing and limiting the negative consequences of monopolization become so important and large-scale in modern conditions that the protection of economic competition, the definition of rules of its conduct and antitrust regulation become a regular function of the state as one of its most important activities. After all, the purpose of regulating the competitive process in the relevant market is to create a favorable environment for competition to perform its functions, realize its potential, first of all - to ensure equal opportunities and conditions of market access for all its participants, to prevent monopolies. The main forms of state regulation of the competitive environment in accordance with the specifics of the industry are proposed, which should cover the following three areas: legal, incentive and imperative. The characteristics of these areas and the main levers of state influence are outlined. It is emphasized that with the help of imperative factors it is possible to ensure the transparency of competitive relations in the confectionery market.
Keywords: рівень монополізації; індекс Хіршмана-Харфінделя; конкурентне середовище; продовольчий ринок; засоби державного впливу; інтенсивність конкурентної боротьби; державне регулювання; уровень монополизации; индекс Хиршмана-Харфинделя; конкурентная среда; продовольственный рынок; средства государственного воздействия; интенсивность конкурентной борьбы; государственное регулирование; level of monopolization; Hirschman-Harfindel index; competitive environment; food market; means of state influence; intensity of competition; state regulation; кафедра маркетингу